Place Management and Crime Ownership and Property Rights as a Source of Social Control - Eck, John E.; Linning, Shannon J.; Herold, Tamara D. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This brief describes the theory and evidence of a form of social control known as place management. Created by property owners, place management is an alternative to the two other domains of social control: formally created by the state and informally created by residents. It helps explain the high concentration of crime and disorder at a relatively small proportion of addresses and facilities. This volume examines the specifics of place management and extends it in three ways: to show how high crime places may radiate crime into their surroundings; to reveal networks of places that create crime hotspot spanning blocks; to demonstrate how networks of place managers influence crime throughout neighborhoods. Finally, it shows that the policy implications of place management extend far beyond the police and should include regulatory policies.
Chapter 1. Introduction - the problem of places and forms of social control -- Chapter 2. 10 reasons some places are bad but most are not -- Chapter 3. The missing form of social control -- place management -- Chapter 4. Where do place managers get their authority? -- Chapter 5. Why some place managers fail -- Chapter 6. The extended place manager I - Networks of places -- Chapter 7. The extended place manager II - Into the neighborhood -- Chapter 8. The extended place manager III - Into cyberspace -- Chapter 9. Regulating places and managers -- Chapter 10. Forms of social control: formal, informal, management.
Keywords: Crime -- Sociological aspects; Criminology; Crime and Society; Criminology